The Role of Banking Service Quality in Adoption Information and Communication Technologies -Sample study for some branches of private banks operating in Lattakia- (Journal of Hama University, 2020)
Banks represent the lifeblood of monetary and financial life in any country in the world as they play a key role in the internal and external trade operations, where the banking sector has recently witnessed accelerated steps towards the development of performance and improve the quality of banking services provided to customers, in order to reach the level of major challenges of competition that Banks are exposed in their business, as the most important characteristic of the banking business is the increasing development of banking technology in order to modernize the systems and means of providing banking services and the creation of new technologies for efficient banking service, which leads to gain more Customers and increase their confidence.This research seeks to identify the role played by the quality of banking service provided in the adoption of information and communication technologies (mobile banking), and in increasing customer loyalty to the bank, where the questionnaire was used to collect data for the views of a sample of employees in private banks operating in Latakia to reach the results Realistic can be used to build conclusions and recommendations to improve the banking service within the banking sector.The most important results of the research are that there is a significant relationship between perceived benefit, perceived ease of use, and customer adoption for the mobile banking service, also the benefit that customers obtain from the banking service and their ease of use have an impact on the customers use of mobile banking technology in their banking dealings.